(untitled) (Revista Espinhaço, 2023)
The historical series of meteorological data has been recorded in the Chapada do Couto region since 2016, seeking to characterize the dynamics of the relation between climatic parameters and hydrological and ecological processes. However, periods of failure in the record of historical series data represent a challenge in long-term studies. Thus, the objective of this study was to evaluate the relation between climatic parameters collected from different sources to allow the imputation of missing values in the data series from the Chapada do Couto, including twelve discontinuous months between 2020 and 2022. Interpolation techniques were used based on two databases, INMET (observed) and ERA5 (reanalysis). The INMET data was obtained from the automatic meteorological station installed in Diamantina-MG (DTA). The ERA5 data were spatially interpolated by the Inverce Distance from four points distributed around the meteorological station intalled in the Chapada do Couto. The data were used in linear regression analysis and the values of the coefficient of determination (R²) and residual standard error (EPR) were evaluated. The daily average and maximum air temperatures, relative air humidity, dew point temperature and precipitation showed strong correlations to both databases, with better predictions from the DTA station, while minimum daily temperature showed higher correlation to the ERA5 data. Precipitation data imputation performed worse when compared to other parameters for both databases. The use of DTA data was more appropriate to support meteorological data imputation in the Chapada do Couto region, although ERA5 also performed as a viable predictor for completing historical series of meteorological data in the region for situations where reliable data records are not available. From the imputed series for the monitoring period, a monthly average temperature of 16.5 °C was calculated during the monitoring period, ranging from 13.3 °C in the coldest month (July) to 18.6 °C in the hottest month (January). The total annual precipitation was on average 1410 mm, with 84% of the volume concentrated between October and March.